Abundance of Collembola and Mites in Hardwickia binata Based Silvopastures in Semi-arid Tracts of Central India - Roy, Sharmlla; Srivastav, A. K.; Roy, M. M. (Indian Forester, 2003)
Quantitative estimations were made for population build-up of soil inhabiting collembola and mites in Hardwickia binata based silvopastures. Temporal distribution pattern showed two peaks of population build up-one major peak during July-September and another peak during December-February. Lower population build up was generally observed during March -June. Mites constituted 86 per cent of the total population, the major group being cryptostigmata (61%) followed by prostigmata (19%) and astigmata + mesostigmata (6%). The significant positive correlation of mite population with soil moisture and RH and collembolan population with RH in such a system was observed.